Multidisciplinary tools for sustainable management of an ecosystem service: The case study of mussel farming in the Mar Piccolo of Taranto (Mediterranean, Ionian Sea). (15th June 2019) - Giordano, Laura; Portacci, Giuseppe; Caroppo, Carmela
Abstract: This paper describes the development of multidisciplinary simulation tools based on a system approach, and its contribution to local political debate on sustainable shellfish farming in a Mediterranean coastal site (Mar Piccolo of Taranto, Ionian Sea). Remote sensing images were used for the first time to count mussel culture plants and to validate information provided by stakeholders and farmers. The data obtained were even more important considering the lack of reliable official statistics. Further, a model was developed to simulate exploratory scenarios. In the modelling platform, the ecosystem and individual mussel growth models (built in the frame of the EU Integrated Project SPICOSA, Science and Policy Integration for Coastal System Assessment) are combined with the Mussel Farm Model (MFM). The simulated scenarios suggested that: 1. Farming is unsustainable, because it exceeds the system carrying capacity; 2. Plant overloading is exacerbated by the negative effects of recurrent heatwaves; 3. Sustainable management measures should be applied to obtain individuals of good quality as well as to extend the juveniles sale period and cope with climate crises. The results show that the described tools may help in the design of viable policies based on operational objectives and feasible technical options. Since until now, production trends cannot be determined based on natural and social factors alone, once applied, this tool will allow for a more exemplary production system. It could also become a good practice example towards a more sustainable development of coastal zones. Highlights: Using remote sensing images for mussel production assessment. Decision-maker supporting tools and exploratory scenarios. Carrying capacity evaluation for mussel culture in a Mediterranean coastal zone. Overloading of mussel plants and environmental crises (hypoxia/anoxia and heatwaves). Providing an example of good practices towards sustainable development in aquaculture.